Studies on Nursery Techniques (Method of Sowing and Optimum Irrigation) of Albizia lebbek (L) Benth under North Indian Moist Tropical Climatic Conditions - Bahuguna, V. K.; Maithani, G. P.; Lal, Pyare (Indian Forester, 1987)
The paper presents the results of an experiment conducted for standardization of best combination of method of sowing and optimum irrigation schedule. Requirements of seeds at the nursery stages is also determined. The results of the experiment indicates that Dibbling method of sowing, with once a day irrigation proves to be the best combinations.